Using co-located radars and instruments to analyse ionespheric events over South Africa - Athieno, Racheal (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2012)
Space weather and its effect on technological systems are important for scientific research. Developing an understanding of the behaviour, sources and effects of ionospheric events form a basis for improving space weather prediction. This thesis attempts to use co-located radars and instruments for the analysis of ionospheric events over South Africa. The HF Doppler radar, ionosonde, Global Positioning System (GPS) and GPS ionospheric scintillation monitor (GISTM) receivers are co-located in Hermanus (34.4Â°S, 19.2Â°E), one of the observatories for the space science directorate of the South African National Space Agency (SANSA). Data was obtained from these radars and instruments and analysed for ionospheric events. Only the Hermanus station was selected for this analysis, because it is currently the only South African station that hosts all the mentioned radars and instruments. Ionospheric events identified include wave-like structures, Doppler spread, sudden frequency deviations and ionospheric oscillations associated with geomagnetic pulsations. For the purpose of this work, ionospheric events are defined as any unusual structures observed on the received signal and inferred from observations made by the HF Doppler radar. They were identified by visual inspection of the Doppler shift spectrograms. The magnitude and nature of the events vary, depending on their source and were observed by all, some or one instrument. This study suggests that the inclusion of a wider data coverage and more stations in South Africa merit consideration, especially since plans are underway to host a co-located radar network similar to that in Hermanus at at least three additional observatory sites in South Africa. This study lays a foundation for multi-station co-located radar and instrument observation and analysis of ionospheric events which should enhance the accuracy of space weather and HF communication prediction.
Keywords: Ionosphere -- Research -- South Africa; Space environment -- Research -- South Africa; Meteorology -- Research -- South Africa; Ionosondes -- Research -- South Africa